Modelling Customer Satisfaction of Smartphones in the Czech Republic - Petr Suchánek; Radovan Sobota (Kvalita Inovácia Prosperita, 2023)
Purpose: The goal of this paper is to model customer satisfaction of smartphone select manufacturers in the Czech Republic (CR). Furthermore, the paper aims to model the factors which affect customer satisfaction of the smartphone.